Ca2+ microdomain-based excitation-transcription coupling in cardiac myocytes and vascular smooth muscle cells - Tsukasa Koide; Wayne R. Giles; Rubii Kondo; Yuji Imaizumi; Hisao Yamamura; Yoshiaki Suzuki (Inflammation and Regeneration, 2025)
Abstract Ca2+ signals play a crucial role in maintaining cardiovascular homeostasis, including regulation of the heartbeat, blood pressure, and adaptation to changes in the external environment. Conversely, abnormal Ca2+ signaling is often involved in the onset and progression of cardiovascular diseases, such as cardiac hypertrophy, heart failure, arteriosclerosis, and hypertension. In excitable cells, such as cardiac myocytes and vascular smooth muscle cells (VSMCs), membrane depolarization, and the subsequent elevation of cytosolic Ca2+ concentration ([Ca2+]cyt) via voltage-dependent Ca2+ channels (VDCCs) cause muscle contraction, which is known as excitation–contraction coupling (E-C coupling). Elevated [Ca2+]cyt can also activate Ca2+-dependent enzymes, in some cases leading to changes in gene expression patterns and contributing to long-term cellular responses. This mechanism is referred to as excitation-transcription coupling (E-T coupling), and it is involved in both the adaptive and pathological responses of the cardiovascular system to chronic stimulation. Specific intracellular regions, known as Ca2+ microdomains, exhibit localized increases in [Ca2+]cyt. Such localized Ca2+ signaling is now known to be one of the molecular mechanisms controlling the diversity of Ca2+ responses. These Ca2+ microdomains are often formed by complexes consisting of Ca2+ channels and downstream Ca2+-dependent enzymes localized by scaffolding proteins. This review outlines some of the molecular mechanisms and roles of Ca2+ microdomain-based E-T coupling in cardiac myocytes and VSMCs. First, we discuss the major molecular components that are essential for functional Ca2+ microdomains. For example, VDCC (CaV1.2 channel), ryanodine receptor (RyR), Ca2+-dependent enzymes (Ca2+/CaM-dependent kinase [CaMK], calcineurin [CaN], and calpain), and scaffolding proteins (A-kinase anchoring proteins [AKAPs], caveolin, and junctophilin). Next, we discuss the roles of Ca2+ microdomain-based E-T coupling in physiological and pathophysiological remodeling in cardiac myocytes and vascular smooth muscle cells.